The psychosocial adjustment of care leavers in their transition to adult independent living (El ajuste psicosocial de jóvenes extutelados en su transición a la vida adulta independiente). Issue 1 (2nd January 2023) - Gullo, Federica; García-Alba, Laura; Bravo, Amaia; del Valle, Jorge F.
ABSTRACT: Youths who come of age in out-of-home care are an especially vulnerable population who transition to adulthood quickly, prematurely and with few resources, which hinders their social integration. This, coupled with their experiences of victimization, means that they suffer from more mental health problems, negative self-concept and lower well-being. The objective of this study was to analyse the psychosocial adjustment of care leavers in terms of self-esteem, well-being and behavioural and emotional problems, as well as the influence of certain sociodemographic variables and variables related to their situations on these dimensions. One hundred and fifty care leavers from different Autonomous Communities in Spain participated in the study. The data were collected via a semi-structured interview and several standardized tests. The bivariate and multivariate analyses conducted revealed lower levels of adjustment among girls, the youngest and those with poorer outcomes and lower supports. The results highlight the importance of taking gender approaches and reinforcing the support provided to this population.